KETERAMPILAN MENULIS TEKS ULASAN DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL SISWA KELAS VIII SMPN 3 X KOTO SINGKARAK SEMESTER II TAHUN AJARAN 2021/2022 - Ratna Ulan Sari; Zona Rida Rahayu; Mega Putri (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2022)
This study aims to describe the skills of writing review texts using audio-visual media for class VIII students of SMPN 3 X Koto Singkarak in the second semester of the 2021/2022 academic year. This type of research is quantitative using a descriptive method. The sample of this research is the students of class VIII SMPN 3 X Koto Singkarak, totaling 30 people. The sampling technique is based on percentage random sampling (proportional random sampling) whose method of withdrawal is based on the proportion of the number of students per class. Data collection techniques in the form of performance tests. Data analysis techniques include reading, checking and scoring student test results, converting raw scores into grades, classifying student scores on a scale of 10, making histograms, and concluding research results in the form of a thesis. The results of the research on writing review text skills using audio visual media, the average value of students' ability in writing review texts using audio visual media on the work identity structure is 85.53 which is in very good qualification, on the orientation structure is 78.85 is in good qualification, in the synopsis structure, 88.87 is in very good qualification, in the analysis structure, 68.86 is in more than adequate qualification, in the evaluation structure 71.07 is in more than adequate qualification. It can be explained that the students of SMPN 3 X Koto Singkarak are able to write a review text correctly. Based on the above qualifications, it can be concluded that the skills of writing review texts using audio-visual media students of class VIII SMPN 3 X Koto Singkarak in the second semester of the 2021/2022 academic year are in good qualifications with a mastery level of 76-85% with an average score of 78.40 .